The Gruffalo - Donaldson, Julia; Scheffler, Axel (ill.) (London Macmillan, 2015)
A mouse took a stroll through the deep dark wood. A fox saw the mouse and the mouse looked good. But the fox is the least of the quick-witted mouse's problems. He is about to come face to face with an Owl, a snake and... Oh help! oh no! A Gruffalo
Contains colourful illustrations.
Keywords: Children-Story